TINGKAT IMPLEMENTASI KEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Fitri, Rozani; Yusran, Fadly Hairannoor; Hadi, Abdul; Razie, Fakhrur (Universitas Lambung Mangkurat, 2023)
Food availability is inseparable from the availability of agricultural land as a strategic function, where cultivation businesses still require agricultural land. The level of implementation of sustainable agricultural land protection policies in Tanah Laut District in Pelaihari District using derivative policy formulations or derivatives of a policy, namely the Regional Regulation of the Regional Spatial Plan (RTRW) of Tanah Laut Regency Number 3 of 2016 to the academic study process, with the results of the Draft Regional Regulation (Raperda) for the Protection of Sustainable Food Agricultural Land which was discussed with the legislature in 2023. Data were obtained from the ground check of academic studies on LP2B land area of 21,399.75 ha, LCP2B covering an area of 4,369.52 ha, land use change covering an area of 3,093.43 ha spread across 11 districts and for Pelaihari District LP2B covering an area of 3,530.75 ha. LCP2B 200.56 ha and land conversion of 90.27 ha, as a completeness of the data proposed in the LP2B Raperda.